Multi-cavity structure microcapsule and preparation method thereof
Patent Information
- Application Number
- CN202611312856.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明的主要目的是提出一种多腔体结构微胶囊及其制备方法,旨在解决现有技术中姜黄素负载率较低的问题
[0015]本发明的技术方案中,油骨架层可以较好地溶解和负载姜黄素等油溶性物质,从而提升对油溶性物质的负载率;此外,油骨架层可以使得油溶性物质在肠胃环境中被缓慢释放;壳层设置在内核结构外层,还能作为对油溶性物质的机械屏障,进一步放缓油溶性物质的释放速度。
Smart Images

Figure CN122954754A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of microcapsule preparation technology, and in particular to a multi-cavity microcapsule and its preparation method. Background Technology
[0002] Curcumin possesses various physiological activities such as antioxidant, anti-inflammatory, and antibacterial properties, and has potential application value in the fields of medicine and food.
[0003] However, curcumin suffers from poor water solubility and low bioavailability, which limits its widespread application.
[0004] Existing methods for delivering curcumin mainly involve adding it to the oil phase and then preparing it as an emulsion or microcapsule. However, this method still has a low loading rate and suffers from difficulties in sustained release. Summary of the Invention
[0005] The main objective of this invention is to propose a multi-cavity microcapsule structure and its preparation method, aiming to solve the problem of low curcumin loading in the prior art.
[0006] To achieve the above objectives, the present invention proposes a microcapsule comprising a shell and a plurality of core structures dispersed within the shell. The core structure includes an oil skeleton layer, and a cavity is formed inside the oil skeleton layer; the oil skeleton layer includes oil and an oil phase emulsifier; The shell comprises proteins, polysaccharides, sugar alcohols, and nanogels.
[0007] In one embodiment, the mass of the oil is N1, the total mass of the protein and polysaccharide in the shell is N2, and the ratio of N1 to N2 ranges from (0.8 to 1.2): 1; and / or, The microcapsules have a particle size of 5 μm to 50 μm.
[0008] In one embodiment, the oil skeleton layer comprises at least one of soybean oil and peanut oil; and / or, The oil-phase emulsifier includes polyglycerol ricinoleate; and / or... The nanogel comprises octenyl succinate starch-lysozyme nanogel; and / or... The protein includes soy protein isolate; and / or, The polysaccharide includes chitosan hydrochloride; and / or, The sugar alcohols include maltitol.
[0009] This invention also provides a method for preparing microcapsules, the method comprising the following steps: S1. Mix the oil phase emulsifier and oil to obtain an oil phase; disperse water in the oil phase to obtain a primary emulsion; S2 provides nanogels; S3. Provide a wall material solution; the solute in the wall material solution includes proteins and polysaccharides; S4. Mix the sugar alcohol, the wall material solution, and the nanogel to obtain a mixture; S5. Disperse the colostrum in the mixture to obtain a bilayer emulsion; spray dry the bilayer emulsion to obtain the microcapsules.
[0010] In one embodiment, in step S1: The volume ratio of the water to the oil phase is (2~3):(7~8); and / or, The oil phase emulsifier has a volume fraction of 6% to 8% in the oil phase; and / or, The dispersion rotation speed is 10000~20000 r / min; and / or, The dispersion time is 2-4 minutes.
[0011] In one embodiment, the nanogel comprises octenyl succinate starch-lysozyme nanogel, and step S2 includes: S21. Mix octenyl succinic acid starch solution and lysozyme solution, stir and heat treat to obtain the octenyl succinic acid starch-lysozyme nanogel.
[0012] In one embodiment, in step S21: The octenyl succinic acid starch solution has a mass concentration of 3% to 6%; and / or... The lysozyme solution has a mass concentration of 8% to 12%; and / or, The volume ratio of the octenyl succinic acid starch solution to the lysozyme solution is (1.8~2.2):1; and / or, The stirring speed is 700~900 rpm; and / or, The stirring process takes 25-35 minutes; and / or, The heat treatment temperature is 70~100℃; and / or, The heat treatment time is 40-60 minutes.
[0013] In one embodiment, in step S5: The volume ratio of the colostrum to the mixture is (1~3):(7~9); and / or, The dispersion rotation speed is 8000~12000 r / min; and / or, The dispersion time is 1.5~2.5 min.
[0014] In one embodiment, in step S4: The sugar alcohol includes maltitol, the total mass of protein and polysaccharide in the wall material solution is M1, the mass of maltitol is M2, and M1 / (M1+M2) = 20%~40%.
[0015] In the technical solution of the present invention, the oil skeleton layer can better dissolve and load oil-soluble substances such as curcumin, thereby improving the loading rate of oil-soluble substances; in addition, the oil skeleton layer can make oil-soluble substances slowly released in the gastrointestinal environment; the shell layer is set outside the core structure and can also serve as a mechanical barrier for oil-soluble substances, further slowing down the release rate of oil-soluble substances. Attached Figure Description
[0016] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0017] Figure 1 Image (a) is an optical microscope image of the microcapsules prepared in Examples 2-4 of this invention; Figure 1 (b) is a fluorescence microscope image of the microcapsules prepared in Examples 2-4 of this application; Figure 1 Image (c) is a scanning electron microscope image of the microcapsules prepared in Examples 2-4 of this invention; Figure 1 (d) shows the particle size results of the microcapsules prepared in Examples 2-4 of this invention; Figure 1 (e) is a graph showing the encapsulation efficiency of curcumin in the microcapsules prepared in Examples 2-4 of this invention; Figure 2 (a) is a cavity distribution diagram of the microcapsules prepared in Examples 2-4 of the present invention; Figure 2 (b) is a graph showing the sustained-release performance test results of the microcapsules prepared in Examples 2-4 of this invention; Figure 3 Image (a) is an optical microscope image of Embodiments 5-6 of the present invention; Figure 3 (b) is a fluorescence microscope image of the microcapsules prepared in Examples 5-6 of this application; Figure 3 Image (c) is a scanning electron microscope image of the microcapsules prepared in Examples 5-6 of this invention; Figure 3 (d) shows the particle size results of the microcapsules prepared in Examples 4-6 of this invention; Figure 3 (e) is a graph showing the encapsulation efficiency of curcumin in the microcapsules prepared in Examples 4-6 of this invention; Figure 4 (a) is a cavity distribution diagram of the microcapsules prepared in Examples 5-6 of the present invention; Figure 4 (b) shows the sustained-release performance test results of the microcapsules prepared in Examples 4-6 of this invention; Figure 5 Image (a) is an optical microscope image of Embodiments 7-8 of the present invention; Figure 5 (b) is a fluorescence microscope image of the microcapsules prepared in Examples 7-8 of this application; Figure 5 Image (c) is a scanning electron microscope image of the microcapsules prepared in Examples 7-8 of this invention; Figure 5 (d) shows the particle size results of the microcapsules prepared in Examples 4 and 7-8 of this invention; Figure 5 (e) is a graph showing the encapsulation efficiency of curcumin in the microcapsules prepared in Examples 4 and 7-8 of this invention; Figure 6 (a) is a cavity distribution diagram of the microcapsules prepared in Examples 7-8 of the present invention; Figure 6 Figure (b) shows the sustained-release performance test results of the microcapsules prepared in Examples 4 and 7-8 of this invention.
[0018] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] Existing methods for delivering oil-soluble substances such as curcumin mainly involve adding them to the oil phase and then preparing them as emulsions or microcapsules. However, this method still has a low loading rate and also suffers from the problem of poor sustained release.
[0021] In view of this, the present invention provides a multi-cavity microcapsule, the microcapsule comprising a shell and a plurality of core structures dispersed within the shell; the core structure comprising an oil skeleton layer, wherein cavities are formed within the oil skeleton layer; the oil skeleton layer comprising oil and an oil phase emulsifier; the shell comprising proteins, polysaccharides, sugar alcohols, and nanogels.
[0022] In the technical solution of the present invention, the oil skeleton layer can better dissolve and load oil-soluble substances such as curcumin, thereby improving the loading rate of oil-soluble substances; in addition, the internal oil skeleton layer enables the oil-soluble substances to be slowly released in the gastrointestinal environment; the shell layer is set outside the core structure and can also serve as a mechanical barrier for oil-soluble substances, further slowing down the release rate of oil-soluble substances.
[0023] It's important to note that the stomach environment is highly acidic and contains pepsin, with a pH of 1.5–3.5. In this environment, the proteins and polysaccharides in the shell contract to form a denser network structure, hindering the penetration of gastric acid into the core structure and resisting the initial breakdown by pepsin. Secondly, the nanogel layer structure within the shell is relatively stable in the acidic environment and does not easily disintegrate, thus further protecting the internal oil-soluble substances from release. In the intestines, however, polysaccharides and proteins swell first, and the nanogel layer and oil skeleton are degraded by intestinal enzymes, slowly releasing the oil-soluble substances.
[0024] In some embodiments, the mass of the oil is N1, the total mass of the protein and polysaccharide in the shell is N2, and the value of N1 / N2 ranges from (0.8 to 1.2):1; and / or, the particle size of the microcapsules is 5 μm to 50 μm.
[0025] The N1 / N2 ratio can range from 0.8:1, 1:1, or 1.2:1, which represents the core-to-wall ratio. The microcapsule particle size can be 5 μm, 30 μm, or 50 μm. Controlling these conditions within a suitable range ensures that the microcapsules have a high loading rate for oil-soluble substances, resulting in a slower release rate of the loaded product in the intestine.
[0026] In some embodiments, the oil skeleton layer comprises at least one of soybean oil and peanut oil; and / or, the oil phase emulsifier comprises polyglycerol ricinoleate; and / or, the nanogel comprises octenyl succinate starch-lysozyme nanogel; and / or, the protein comprises soy protein isolate; and / or, the polysaccharide comprises chitosan hydrochloride; and / or, the sugar alcohol comprises maltitol. Simultaneously controlling the types of oil skeleton, oil phase emulsifier, nanogel, protein, polysaccharide, and sugar alcohol within the above-mentioned ranges can ensure a good loading rate of oil-soluble substances and sustained-release effect of the microcapsules.
[0027] This invention also provides a method for preparing microcapsules, the method comprising the following steps: Step S1: Mix the oil phase emulsifier and oil to obtain the oil phase; disperse water in the oil phase to obtain the primary emulsion; Step S2: Provide nanogel; Step S3: Provide a wall material solution; the solute in the wall material solution includes proteins and polysaccharides; Step S4: Mix the sugar alcohol, the wall material solution, and the nanogel to obtain a mixture; Step S5: Disperse the colostrum in the mixture to obtain a bilayer emulsion; spray dry the bilayer emulsion to obtain the microcapsules.
[0028] In the technical solution of this invention, in step S1, the primary emulsion is a water-in-oil system, suitable for loading oil-soluble substances such as curcumin, and these lipophilic substances can be well encapsulated in the oil phase. In step S2, the nanogel can act as an emulsifier for the subsequent aqueous phase, thereby improving the interfacial stability of the subsequent bilayer emulsion. Polysaccharides and proteins have good film-forming properties and water solubility, making them suitable spray-drying wall materials. In step S5, the primary emulsion is dispersed into the mixture to obtain a bilayer emulsion. After the system is dried, the nanogel, polysaccharides, and proteins can act as a mechanical barrier to protect and sustain the release of the loaded oil-soluble substances. The microcapsules prepared by this invention have a high loading rate for oil-soluble substances and a good sustained-release effect. It should be noted that in step S5, the solvent in the mixture is water, which serves as the outer aqueous phase of the bilayer emulsion.
[0029] In some embodiments, in step S1: the volume ratio of water to oil phase is (2~3):(7~8); and / or, the volume fraction of oil phase emulsifier in the oil phase is 6%~8%; and / or, the dispersion rotation speed is 10000~20000 r / min; and / or, the dispersion time is 2~4 min. The volume ratio of water to oil phase can be 2:8, 2.5:7.5, or 3:7, the volume fraction of oil phase emulsifier in the oil phase can be 6%, 7%, or 8%, the dispersion rotation speed can be 10000 r / min, 18000 r / min, or 20000 r / min, and the dispersion time can be 2 min, 3 min, or 4 min. Simultaneously controlling the above parameters within a suitable range can ensure that water is dispersed more uniformly and stably in the oil, forming a more uniform primary emulsion.
[0030] In some embodiments, the nanogel comprises octenyl succinate starch-lysozyme nanogel, and step S2 includes: Step S21: Mix the octenyl succinic acid starch solution and the lysozyme solution, stir and heat treat to obtain the octenyl succinic acid starch-lysozyme nanogel.
[0031] In the technical solution of the present invention, during the mixing and stirring process in step S21, since lysozyme carries a positive charge in the neutral solution and octenyl succinic acid starch (OSA starch) carries a negative charge due to the octenyl succinic acid group, the two will initially combine by attracting each other through electrostatic attraction when mixed; while during the water bath heating process, lysozyme denatures due to heat, and the hydrophobic amino acids that were originally inside the molecule are exposed. The exposed hydrophobic amino acids aggregate with each other under the water transport interaction between molecules, causing the originally loose electrostatic complex to crosslink and shrink, forming a tightly structured nanogel that is not easy to dissociate.
[0032] It should be noted that the nanogel can be obtained by mixing and stirring octenyl succinate starch (OSA starch) and lysozyme, followed by heating in a water bath at 80-85°C. In some embodiments, in step S11: the mass concentration of octenyl succinate starch in the octenyl succinate starch solution is 3%-6%; and / or, the mass concentration of lysozyme solution in the lysozyme solution is 8%-12%; and / or, the volume ratio of the octenyl succinate starch solution to the lysozyme solution is (1.8-2.2):1; and / or, the stirring speed is 700-900 rpm; and / or, the stirring time is 25-35 min; and / or, the heat treatment temperature is 70-100°C; and / or, the heat treatment time is 40-60 min. The mass concentration of octenyl succinic acid starch in the octenyl succinic acid starch solution can be 3%, 4%, 5%, or 6%, and the mass concentration of lysozyme solution in the lysozyme solution can be 8%, 10%, or 12%. The volume ratio of octenyl succinic acid starch solution to lysozyme solution can be 1.8:1, 2:1, or 2.2:1. The stirring speed can be 700 rpm, 800 rpm, or 900 rpm, and the stirring time can be 25 min, 30 min, or 35 min. The heat treatment temperature can be 70℃, 90℃, or 100℃, and the heat treatment time can be 40 min, 50 min, or 60 min. Controlling these parameters within a suitable range ensures good cross-linking strength of the obtained octenyl succinic acid starch-lysozyme nanogel.
[0033] In some embodiments, in step S5: the volume ratio of the primary emulsion to the mixture is (1~3):(7~9); and / or, the dispersion rotation speed is 8000~12000 r / min; and / or, the dispersion time is 1.5~2.5 min. The volume ratio of the primary emulsion to the mixture can be 1:9, 2:8, or 3:7, the dispersion rotation speed can be 8000 r / min, 10000 r / min, or 12000 r / min, and the dispersion time can be 1.5 min, 2 min, or 2.5 min. Controlling the above conditions within a suitable range can ensure high stability of the bilayer emulsion.
[0034] In some embodiments, in step S4: the sugar alcohol includes maltitol, the total mass of protein and polysaccharide in the wall material solution is M1, the mass of maltitol is M2, and M1 / (M1+M2) = 20%~40%. That is, the value of M1 / (M1+M2) can be 20%, 30%, or 40%, preferably 40%. At this point, a multi-cavity structure can be formed because a high proportion of wall material can improve the stability of internal oil droplets, thereby ensuring that the relative structure of each component is stable after spray drying and that the fusion phenomenon is not obvious.
[0035] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0036] Example 1 A microcapsule is prepared by the following steps: (1) Preparation of W1 / O (water-in-oil) colostrum: Polyglycerol ricinoleate (PGPR) (7%, v / v) was dissolved in peanut oil and magnetically stirred at room temperature for 30 min until the PGPR was fully dissolved to obtain the oil phase. Deionized water was added to the oil phase at a volume ratio of 2:8 (water phase to oil phase) and dispersed at 18000 r / min for 3 min using a high-speed disperser to obtain the W1 / O primary emulsion.
[0037] (2) Preparation of soybean protein isolate / chitosan hydrochloride complex: Soy protein isolate (SPI) was dispersed in water and stirred at 800 rpm for 4 hours to obtain a dispersion. The dispersion was then ultrasonically dispersed using an ultrasonic cell disruptor at a power of 360 W for 12 minutes (with an ultrasonic pulse duration of 4 seconds on and 5 seconds off). The solution was then incubated overnight at 4°C to allow complete hydration of the SPI, yielding an SPI solution. Chitosan hydrochloride (CHC, with the same mass as SPI, i.e., a 1:1 mass ratio) was added to the SPI solution to adjust the pH to 6.0. The mixture was stirred until the CHC was fully dissolved, yielding an SPI / CHC complex solution.
[0038] (3) Preparation of octenyl succinic acid starch-lysozyme nanogel: Octenyl succinate starch (OSA starch) was dissolved in 20 mL of deionized water to a concentration of 5% (w / v), and stirred at 800 rpm for 5 h on a magnetic stirrer to obtain an OSA solution. Lysozyme was dissolved in 10 mL of deionized water to a concentration of 10% (w / v), and stirred at 800 rpm for 5 h on a magnetic stirrer to obtain a lysozyme solution. The OSA solution and lysozyme solution were mixed and stirred at 800 rpm for 30 min on a magnetic stirrer, and then heated in an 80°C water bath for 50 min to obtain an OSA starch-lysozyme nanogel (in solution state).
[0039] (4) Preparation of multi-cavity microcapsules mediated by bilayer emulsion method A solution of the SPI / CHC complex and maltitol were added to OSA starch-lysozyme nanogel as the wall material solution (as the external aqueous phase) for microcapsules. The mass of SPI+CHC accounted for 20% of the total mass of SPI+CHC+maltitol. The core-to-wall ratio of the microcapsules was fixed at 1:1. The W1 / O primary emulsion was added to the wall material solution at a volume ratio of 1:9 (primary emulsion: external aqueous phase). The mixture was dispersed at 10000 r / min for 2 min using a high-speed disperser to form a W1 / O / W2 (i.e., water-in-oil-in-water, with the external aqueous phase W2 encapsulating the oil phase O, and the oil phase O encapsulating the internal aqueous phase W1) bilayer emulsion. The mixture was then spray-dried to prepare multi-cavity microcapsules.
[0040] Example 2 The difference between Example 2 and Example 1 is that: In step (1), curcumin was also added to the oil phase. The concentration of curcumin in the oil phase was 0.3% (w / v). The other steps were the same as in Example 1. Finally, microcapsules containing curcumin were prepared.
[0041] Example 3 The difference between Example 3 and Example 2 is that: In step (4), the mass of SPI+CHC accounts for 30% of the total mass of SPI+CHC+maltitol.
[0042] Example 4 The difference between Example 4 and Example 2 is that: In step (4), the mass of SPI+CHC accounts for 40% of the total mass of SPI+CHC+maltitol.
[0043] Example 5 The difference between Example 5 and Example 4 is that: The mass ratio of SPI to CHC is 1.5:1.
[0044] Example 6 The difference between Example 6 and Example 4 is that: The mass ratio of SPI to CHC is 2:1.
[0045] Example 7 The difference between Example 7 and Example 4 is that: The volume ratio of colostrum to external aqueous phase is 2:8.
[0046] Example 8 The difference between Example 8 and Example 4 is that: The volume ratio of colostrum to external aqueous phase is 3:7.
[0047] Performance testing 1. Effects of different SPI and CHC contents (i.e., the proportion of the outer shell) on microcapsule structure The particle size, morphology, cavity distribution, and sustained-release performance of the microcapsules prepared in Examples 2-4 were tested: (1) Morphology: The results observed by optical microscope are as follows Figure 1 As shown in (a); the results observed by fluorescence microscopy are as follows. Figure 1 As shown in (b), the fluorescent substance is the oil phase component; the results observed by scanning electron microscopy (SEM) are as follows. Figure 1 As shown in (c); (2) Particle size: obtained by particle size analyzer; results are as follows Figure 1 As shown in (d); (3) Encapsulation efficiency of curcumin: obtained by UV-Vis spectrophotometry, the results are as follows: Figure 1 As shown in (e); (4) Cavity distribution: The microcapsules were subjected to liquid nitrogen brittle fracture treatment and observed by scanning electron microscopy. The results are as follows: Figure 2 As shown in (a); (5) Sustained-release performance: The microcapsule samples were placed in simulated gastric juice, and the temperature was kept constant at 37℃, the stirring speed was 100 rpm, and the reaction was carried out with magnetic stirring for 2 h to simulate the gastric digestion process. After adjusting the pH of the system to 6.8 and terminating the simulated gastric digestion, simulated intestinal juice was added to the system, and the reaction was carried out at the same temperature and stirring conditions as the simulated gastric digestion for 4 h to simulate the intestinal digestion process. The results are as follows. Figure 2 As shown in (b).
[0048] Depend on Figure 1 (a) and Figure 1 As shown in (b), the microcapsules are uniformly dispersed in aqueous solution in spherical form, and the new oil phase is successfully encapsulated in the SPI / CHC shell at all proportions without rupture or leakage. Figure 1 As shown in (c), the surface of the microcapsule is smooth and there are no cracks.
[0049] Depend on Figure 1 As shown in (d), the particle size of the microcapsules decreased significantly with the increase of SPI / CHC content, from 14 μm to 8 μm. This may be because with the increase of SPI / CHC content, more wall material (i.e., SPI / CHC complex) is adsorbed at the oil-water interface, reducing interfacial tension, promoting droplet dispersion, and forming smaller and more uniform droplets.
[0050] Depend on Figure 1 As shown in (e), the encapsulation efficiency of curcumin increases with the increase of SPI / CHC addition. This may be because curcumin is uniformly dispersed in the oil phase and can fully bind to the sites on the wall material, and is stably encapsulated in the wall material during the spray drying process.
[0051] The cavity structure of microcapsules with different SPI / CHC contents is composed of Figure 2 As shown in (a), when the SPI / CHC content was 20% and 30%, the microcapsules did not exhibit a multi-cavity structure. When the SPI / CHC content increased to 40%, the microcapsules exhibited a multi-cavity structure. This may be because a higher SPI / CHC content can improve the strength of the oil-water interface of the microcapsules, thereby maintaining the stability of the internal oil droplets.
[0052] Release characteristics of microcapsules with different SPI / CHC contents, such as Figure 2 As shown in (b), when the SPI / CHC addition was 40%, the microcapsules exhibited the lowest curcumin release rate during simulated gastric digestion and a better sustained-release effect during intestinal digestion. This is likely due to the higher SPI / CHC addition increasing the density of the wall material network.
[0053] 2. Effect of different wall material ratios (SPI:CHC) on microcapsule properties The particle size, morphology, cavity distribution, and sustained-release performance of the microcapsules prepared in Examples 4-6 were tested. The test method is the same as in performance test 1 (1)-(5), and the results are as follows: Figure 3 (a) Figure 3 (b) Figure 3 (c) Figure 3 (d) Figure 3 (e) Figure 4 (a) and Figure 4 As shown in (b).
[0054] Depend on Figure 3 (a) and Figure 3 As shown in (b), under different SPI:CHC ratios, all microcapsules exhibit uniform dispersion in aqueous solution and are spherical, with the oil phase (red) successfully embedded in the wall material.
[0055] Depend on Figure 3 As shown in (c), the microcapsules at all ratios exhibit a relatively smooth spherical shape. However, as the CHC ratio increases, slight adhesion appears on the surface of the microcapsules. This may be attributed to the fact that excessive CHC enhances the surface adhesion of the wall material, thereby weakening the electrostatic repulsion between microcapsules and leading to a decrease in particle dispersion.
[0056] Depend on Figure 3 (d) and Figure 3 As shown in (e), the particle size of the microcapsules and the encapsulation efficiency of curcumin did not change significantly with the increase of the SPI:CHC ratio, indicating that the microcapsules have a relatively stable structure at all ratios.
[0057] Depend on Figure 4 As shown in (a), the microcapsules have a multi-cavity structure under all SPI:CHC ratios. This may be because all groups of microcapsules have good stability and can effectively prevent the aggregation of oil droplets during spray drying.
[0058] Depend on Figure 4 As shown in Figure (b), the microcapsules in all groups had low release rates during SGF incubation and good sustained-release effects during simulated intestinal digestion.
[0059] 3. Effect of different emulsion-to-water ratios (W1 / O:W2) on the properties of microcapsules The particle size, morphology, cavity distribution, and sustained-release performance of the microcapsules prepared in Examples 4 and 7-8 were tested, and the test methods were the same as those in Performance Test 1 (1-5). The results are as follows: Figure 5 (a) Figure 5 (b) Figure 5 (c) Figure 5(d) Figure 5 (e) Figure 6 (a) and Figure 6 As shown in (b).
[0060] Depend on Figure 5 (a) and Figure 5 As shown in (b), the microcapsules are spherical and well dispersed under various W1 / O:W2 ratios. The red fluorescence signal under the fluorescence field completely coincides with the position of the microcapsules under the bright field, indicating that the oil phase components are successfully embedded inside the microcapsules.
[0061] Depend on Figure 5 As shown in (c), the microcapsules have a complete spherical structure with a relatively smooth surface. Some samples have slight depressions, which may be caused by the rapid water loss and shrinkage of the SPI / CHC shell during the spray drying process. This is a typical morphological feature of microcapsules prepared by spray drying.
[0062] Depend on Figure 5 (d) and Figure 5 As shown in (e), with the increase of W1 / O:W2, the encapsulation rate of curcumin decreased from 83% to 73%. This may be due to the higher proportion of external water phase forming a thicker wall structure, which reduces the curcumin loss caused by high temperature during spray drying.
[0063] Depend on Figure 6 As shown in Figure (a), the cross-section of the partially ruptured microcapsules reveals that when the W1 / O:W2 ratio is 2:8, the microcapsules exhibit a multi-cavity structure; however, when the W1 / O:W2 ratio increases to 3:7, the multi-cavity structure disappears. This may be because when the W1 / O content is low, it can form a stable and discrete droplet structure inside the microcapsule; while as the W1 / O ratio increases, the stability of the dual emulsion system decreases, and the oil droplets aggregate during spray drying, eventually forming a single cavity.
[0064] Depend on Figure 6 As shown in Figure (b), when the W1 / O:W2 ratio was 1:9, the curcumin release rate after 2 hours of incubation in SGF was only 7%; however, when the ratio increased to 3:7, the curcumin release increased to 29%. This is because a thicker shell structure was formed outside the oil phase when the W1 / O:W2 ratio was 1:9, thus the microcapsules could better protect curcumin in the gastric environment, preventing its premature release before reaching the site of action. After entering the intestinal simulated digestion stage, the release rate of the microcapsules significantly increased. After 2 hours of simulated digestion, the cumulative release rate of the microcapsule group with a W1 / O:W2 ratio of 3:7 reached 91%, while the cumulative release rate of the microcapsule group with a W1 / O:W2 ratio of 1:9 was 57%, and a gradual release trend was observed throughout the SIF stage.
[0065] In summary, in this application, when the mass ratio of SPI to CHC is 1:1, there is an optimal condition: as shown in Example 4, when the volume ratio of the promulgated emulsion and the external aqueous phase is simultaneously controlled at 1:9, and the mass percentage of the SPI / CHC complex solution in the system is 40%, a multi-cavity microcapsule structure can be synergistically constructed, thereby ensuring a slower release rate of curcumin loaded in the microcapsules. As shown in Example 2, when the volume ratio of the promulgated emulsion and the external aqueous phase is simultaneously controlled at 1:9, and the mass percentage of the SPI / CHC complex solution in the system is 20%, a multi-cavity microcapsule structure cannot be systematically constructed, resulting in a relatively faster release rate of curcumin loaded in the microcapsules. This indicates a synergistic effect between different parameters.
[0066] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.
Claims
1. A microcapsule, characterized in that, The microcapsule includes a shell and multiple core structures dispersed within the shell. The core structure includes an oil skeleton layer, and a cavity is formed inside the oil skeleton layer; the oil skeleton layer includes oil and an oil phase emulsifier; The shell comprises proteins, polysaccharides, sugar alcohols, and nanogels.
2. The microcapsule as described in claim 1, characterized in that, The mass of the oil is N1, the total mass of the protein and polysaccharide in the shell is N2, and the ratio of N1 to N2 ranges from (0.8 to 1.2): 1; and / or, The microcapsules have a particle size of 5 μm to 50 μm.
3. The microcapsule as described in claim 1, characterized in that, The oil skeleton layer includes at least one of soybean oil and peanut oil; and / or, The oil-phase emulsifier includes polyglycerol ricinoleate; and / or... The nanogel comprises octenyl succinate starch-lysozyme nanogel; and / or... The protein includes soy protein isolate; and / or, The polysaccharide includes chitosan hydrochloride; and / or, The sugar alcohols include maltitol.
4. A method for preparing microcapsules as described in any one of claims 1 to 3, characterized in that, The method for preparing the microcapsules includes the following steps: S1. Mix the oil phase emulsifier and oil to obtain an oil phase; disperse water in the oil phase to obtain a primary emulsion; S2 provides nanogels; S3. Provide a wall material solution; the solute in the wall material solution includes proteins and polysaccharides; S4. Mix the sugar alcohol, the wall material solution, and the nanogel to obtain a mixture; S5. Disperse the colostrum in the mixture to obtain a bilayer emulsion; spray dry the bilayer emulsion to obtain the microcapsules.
5. The method for preparing microcapsules as described in claim 4, characterized in that, In step S1: The volume ratio of the water to the oil phase is (2~3):(7~8); and / or, The oil phase emulsifier has a volume fraction of 6% to 8% in the oil phase; and / or, The dispersion rotation speed is 10000~20000 r / min; and / or, The dispersion time is 2-4 minutes.
6. The method for preparing microcapsules as described in claim 4, characterized in that, The nanogel comprises octenyl succinate starch-lysozyme nanogel, and step S2 includes: S21. Mix octenyl succinic acid starch solution and lysozyme solution, stir and heat treat to obtain the octenyl succinic acid starch-lysozyme nanogel.
7. The method for preparing microcapsules as described in claim 6, characterized in that, In step S21: The octenyl succinic acid starch solution has a mass concentration of 3% to 6%; and / or... The lysozyme solution has a mass concentration of 8% to 12%; and / or, The volume ratio of the octenyl succinic acid starch solution to the lysozyme solution is (1.8~2.2):1; and / or, The stirring speed is 700~900 rpm; and / or, The stirring process takes 25-35 minutes; and / or, The heat treatment temperature is 70~100℃; and / or, The heat treatment time is 40-60 minutes.
8. The method for preparing microcapsules as described in claim 4, characterized in that, In step S5: The volume ratio of the colostrum to the mixture is (1~3):(7~9); and / or, The dispersion rotation speed is 8000~12000 r / min; and / or, The dispersion time is 1.5~2.5 min.
9. The method for preparing microcapsules as described in claim 4, characterized in that, In step S4: The sugar alcohol includes maltitol, the total mass of protein and polysaccharide in the wall material solution is M1, the mass of maltitol is M2, and M1 / (M1+M2) = 20%~40%.